2009
DOI: 10.1124/jpet.109.156349
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Phencyclidine-Induced Object Recognition Deficits by the Combination of Atypical Antipsychotic Drugs and Pimavanserin (ACP 103), a 5-Hydroxytryptamine2A Receptor Inverse Agonist

Abstract: Subchronic administration of the N-methyl-D-aspartate receptor antagonist, phencyclidine (PCP), in rodents has been shown to produce impairment in novel object recognition (NOR), a model of visual learning and memory. We tested the hypothesis that the selective 5-HT 2A inverse agonists, pimavanserin and, would potentiate subeffective doses of atypical antipsychotic drugs (APDs) to reverse the NOR deficits. Female rats received vehicle or PCP (2 mg/kg b.i.d.) for 7 days, followed by a 7-day washout. Pimavanseri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
73
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 35 publications
9
73
0
Order By: Relevance
“…As mentioned above, these results are in agreement with the lack of effectiveness of these drugs to acutely reverse the effects of subchronic PCP on NOR (Grayson et al, 2007;Snigdha et al, 2010). Subchronic treatment with haloperidol also did not reverse the NOR deficit induced by subchronic PCP in mice (Hashimoto et al, 2005;Nagai et al, 2009).…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…As mentioned above, these results are in agreement with the lack of effectiveness of these drugs to acutely reverse the effects of subchronic PCP on NOR (Grayson et al, 2007;Snigdha et al, 2010). Subchronic treatment with haloperidol also did not reverse the NOR deficit induced by subchronic PCP in mice (Hashimoto et al, 2005;Nagai et al, 2009).…”
Section: Discussionsupporting
confidence: 79%
“…The results in this study are consistent with the acute reversal studies in which atypical APDs, including lurasidone and the 5-HT 1A agonist, tandospirone, but not pimavanserin or haloperidol, are effective reversing PCPinduced cognitive deficits (Grayson et al, 2007;Snigdha et al, 2010;Horiguchi et al, 2011a, b;Horiguchi and Meltzer, 2012). It is of interest to compare these results from acute reversal studies with studies in mice that showed a subchronic PCP (10 mg/kg)-induced NOR deficit in mice and examined the ability of subsequent subchronic administration of APDs to reverse the impairment (Hashimoto et al, 2005;Hagiwara et al, 2008;Nagai et al, 2009;Tanibuchi et al, 2009).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations